Differential hypermethylation of the VTRNA2-1 promoter in hepatocellular carcinoma as a prognostic factor: Tumor marker prognostic study. (July 2020) - Yu, Ming-Chin; Lee, Chao-Wei; Lin, Chia-Hung; Wu, Chun-Hsing; Lee, Yun-Shien; Tsai, Chia-Lung; Tsai, Chi-Neu
Abstract: Background: Vault RNA 2–1 (VTRNA2-1, also called nc886 ) is a 108-nucleotide noncoding transcript that is epigenetically controlled via 18 CpG dinucleotide modifications of its promoter, and can exert either tumor suppressor or oncogenic functions depending on cell types of cancers. In hepatocellular carcinoma (HCC), the role of VTRNA2-1 in prognosis of patients remains unexplored. Here, we analysed the methylation status of the VTRNA2-1 promoter and its correlation with clinical parameters in patients with HCC. Patients and methods: A total of 92 patients with HCC were enrolled, genomic DNA of tumor versus normal tissues were extracted and bisulfite modified. VTRNA2-1 promoter regions chr5: 135416381 (cg06536614), 135416388, 135416394 (cg26328633), and 135416398 (cg25340688) were PCR amplified and pyrosequenced. The methylation status of VTRNA2-1 in patients was further analysed with other clinical parameters via univariate and multivariate analysis. Results: The differential hypermethylation status (tumor- normal) of the VTRNA2-1 promoter in HCC correlated well with the presence of large tumor size ( p  = 0.001), pathological vascular invasion ( p  = 0.036), tumor recurrence ( p  = 0.007) and more advanced tumor stage (stage III AJCC) in patients ( p  = 0.03). In addition, the methylation of the VTRNA2-1 promoter increased in stage III HCC tumor compared with stage I & II tumor (64.7% versus 36.0%, p  = 0.030). Furthermore, the differential hypermethylation status of the VTRNA2-1 promoter was an independent factor for patient outcome after partial hepatectomy using multivariate Cox regression analysis ( p  = 0.011, HR = 2.305). Using another public dataset (GSE89852), we found that the differential hypermethylation of the VTRNA2-1 promoter was also significantly associated with tumor recurrence. Conclusions: Patients had unfavourable outcomes when the VTRNA2-1 promoter was differentially hypermethylated in tumor tissues compared to its adjacent normal tissues. These findings suggest that such patients should receive intensive follow-up care or possible adjuvant therapy after liver resection. Highlights: Differential hypermethylation of the VTRNA2-1 promoter exists in hepatocellular carcinoma (HCC). Hypermethylation of VTRNA2-1 promoter correlated well with tumor aggressiveness. VTRNA2-1 promoter hypermethylation was an independent factor for patients with HCC.